(untitled) (Academia Journal of Medicine, 2020)
Background: DM is the leading cause of end-stage renal disease (ESRD), non-traumatic lower extremity amputations, and adult blindness. It also predisposes to cardiovascular diseases. With an increasing incidence worldwide, DM will be likely a leading cause of morbidity and mortality in the future29. Chronic kidney disease (CKD) encompasses a spectrum of different pathophysiologic processes associated with abnormal kidney function and a progressive decline in glomerular filtration rate. Subjects and Methods: A written informed consent was obtained from all patients. History regarding the duration of hypertension, the medications being taken, coexisting medical problems, and symptomatology suggestive of ischemic heart disease, transient ischemic attacks and that of renal involvement were documented. A detailed history, anthropometry, vital signs, clinical examination and laboratory parameters were recorded for both the study group. Results: The Study reveals that, there was statistically very highly significant difference of age among Type 2 diabetes mellitus with CKD and Non-diabetic patients with CKD (P<0.001).Type 2 diabetes mellitus with CKD cases had significantly higher mean age as compare to Non-diabetic patients with CKD cases. Conclusion: There was statistical significant difference of mean serum uric acid among vegetarians and non-vegetarians with CKD patients (P>0.05).It’s found that vegetarians have less SUA level when compare to mixed diet patients.